Microbial composition, rumen fermentation parameters, enteric methane emissions, and lactational performance of phenotypically high and low methane-emitting dairy cows - N. Stepanchenko; H. Stefenoni; M. Hennessy; I. Nagaraju; D.E. Wasson; S.F. Cueva; S.E. Räisänen; C.D. Dechow; D.W. Pitta; A.N. Hristov (Journal of Dairy Science, 2023)
ABSTRACT: This experiment was designed to investigate the relation of high and low methane-yield phenotypes with body weight (BW), dry matter intake (DMI), lactation performance, enteric CH4 emissions, and rumen fermentation parameters in lactating dairy cows. A total of 130 multi- and primiparous Holstein cows were screened for enteric CH4 emissions using the GreenFeed system (C-Lock Inc.). Out of these 130 cows, 5 were identified as phenotypically high (HM) and 5 as phenotypically low (LM) CH4 emitters. Cows in the LM group had lower daily enteric CH4 emissions than cows in the HM group (on average 346 vs. 439 g/d, respectively), lower CH4 yield (15.5 vs. 20.4 g of CH4/kg of DMI), and CH4 intensity (13.2 vs. 17.0 g of CH4/ kg of energy-corrected milk yield). Enteric emissions of CO2 and H2 did not differ between HM and LM cows. These 10 cows were blocked by parity, days in milk, and milk production, and were used in a 5-wk randomized complete block design experiment. Milk composition, production, and BW were also not different between LM and HM cows. The concentration of total volatile fatty acids in ruminal contents did not differ between CH4 phenotypes, but LM cows had a lower molar proportion of acetate (57 vs. 62.1%), a higher proportion of propionate (27.5 vs. 21.6%, respectively), and therefore a lower acetate-to-propionate ratio than HM cows. Consistently, the 16S cDNA analysis revealed the abundance of Succinivibrionaceae and unclassified Veillonellaceae to be higher in LM cows compared with HM cows, bacteria that were positively correlated with ruminal propionate concentration. Notably, Succinivibrionaceae trigger the formation of propionate via oxaloacetate pathway from phosphoenolpyruvate via Enzyme Commission: 4.1.1.49, which showed a trend to be higher in LM cows compared with HM cows. Additionally, LM cows possessed fewer transcripts of a gene encoding for methyl-CoM reductase enzyme compared with HM. In this study, low and high CH4-yield cows have similar production performance and milk composition, but total-tract apparent digestibility of organic matter and fiber fractions was lower in the former group of animals.